Need for relatedness and eating behaviour in millennials - Escandon-Barbosa, Diana; Salas-Paramo, Jairo (Business: Theory and Practice, 2024)
This research analyses the moderating effects of the need for relatedness in the relationship between behavioural intention (attitude towards the behaviour, subjective norm behaviour and perceived behavioural control) and self-reported healthy eating behaviour in millennials. A structural equation model was used in a sample of 2380 young people in Colombia and Spain (1190 for each country) considered healthy food consumers. All of them were classified as millennials based on age (25–34). The results show that attitudes towards the behaviour and subjective norm behaviour positively influence self-reported healthy eating behaviour.In contrast, perceived control behaviour does not influence self-reported healthy eating behaviour. The need for relatedness moderates the relationship between behavioural intention (attitude towards the behaviour, subjective norm behaviour and perceived behavioural control) and self-reported healthy eating behaviour. The results suggest that the isolation conditions caused by the pandemic directly affect millennials’ behaviour regarding the consumption of healthy food. This condition affects their lifestyles and preferences associated with consumption.